Pengaruh Literasi Keuangan Dan Pengendalian Diri Terhadap Perilaku Keuangan Pada Pelaku UMKM Kelurahan Harjosari I Medan - Gunawan, Heri; Wijaya, Muslim (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
The aim of this research is to partially and simultaneously determine the influence of financial literacy and the influence of self-control on financial behavior among MSMEs in Harjosari I Village, Medan. This type of research uses associative research. In this research, quantitative methods were used with data collection techniques using questionnaires. The population in this study was all 33 MSMEs in Harajosari I Medan Village. Saturated sampling technique is a sampling technique used which means all members of the population are used as samples. The data analysis technique used in this research is the multiple linear regression method using SPSS version 29 software. The results of this research partially show that financial literacy (X1) has a positive and significant effect on financial behavior (Y). Partially, self-control (X2) has a positive and significant effect on financial behavior (Y). And simultaneously financial literacy (X1) and self-control (X2) have a positive and significant effect on financial behavior (Y). Harjosari I Village, Medan.